Bibliometric Analysis in the Context of Earthquake and Türkiye - İbrahim Halil Çelik (Doğal Afetler ve Çevre Dergisi)
Türkiye has experienced many earthquakes of different magnitudes throughout history. Since the destructive consequences of these earthquakes lead to disasters, they have an important place in terms of disaster management. Considering the seismicity of Türkiye, this study aims to present a bibliometric analysis of the studies on earthquakes and Türkiye from the Web of Science (WOS) database. In the study, filters were applied within the framework of various criteria, and analyses were made in the VOSviewer program. Within the scope of the study, it was determined that studies on Earthquake & Türkiye have increased in recent years, the journal with the most publications is Geophysical Journal International, and the most cited study is “Progressive failure on the North Anatolian fault since 1939 by earthquake stress triggering”.It was determined that Barka, Aykut stand out among the authors regarding total link strength and citations, and Ergintav, Semih regarding number of documents and co-authorship. In terms of countries, the USA is the country with the most publications after Türkiye. In terms of keywords, earthquake, Türkiye and the North Anatolian Fault Zone came to the fore. It is thought that this study will be an important reference for researchers who want to study earthquakes in Türkiye.